The Influence of the Research-based Monograph to Improve Pre-Service Teachers’ Knowledge, Attitude, and Behavior - Suryani, S. D.; Amin, M.; Rohman, F. (Jurnal Pendidikan IPA Indonesia, 2021)
This study intends to analyze the influence of the research-based monograph book as a learning resource to improve pre-service teachers’ knowledge, attitudes, and behavior towards the environment. This study is a quasi-experimental study using the Nonequivalent Control Group design. The research sample is 67 pre-service biology teachers using Cluster Sampling. Data were collected using environmental literacy instruments and analyzed descriptively and using the ANCOVA test. The results of the ANCOVA test showed that there was a significant effect on the use of the monograph book on environmental literacy. Knowledge domain obtained 0.047, attitude domain 0.186, and behavioral field 0.986 This research concludes that using the monograph book in learning affects aspects of ecological and environmental knowledge. Nevertheless, it has not had a significant effect on parts of attitude and behavior.